Counts of live embryos and planula larvae of the antipatharian coral Antipathella wollastoni exposed to different seawater temperatures - Maria Rakka; António Godinho; Marina Carreiro-Silva (PANGAEA, 2023)
The antipatharian coral Antipathella wollastoni is commonly found in the Macaronesia (Cape Verde, Madeira, Canaries and the Azores Archipelago). In the Azores Archipelago the species forms dense populations and coral gardens on island slopes between 15-520 m water depth. Here, we present data from two experiments on the embryo and larval survival of A. wollastoni under two different seawater temperatures (21°C and 23°C). Embryos were collected after spawning of mother colonies in aquaria. In the first experiment, we monitored the number of embryos for 24 h after spawning, while in the second experiment we monitored the number of embryos and planulae (larvae) for a total of 35 h.